Occupational for elementary students to raise safety and health awareness at schools and homes - Maharani, Fandita Tonyka; Utari, Dyah (Community Empowerment, 2021)
Elementary school children are in a very important development in their life, which includes physical, mental and perceptual development. Therefore, environmental conditions in schools and homes must be able to support this development. One of them needs to build awareness in elementary students about the dangers and risks of Occupational Safety and Health. This educational activity can reduce the risk of elementary students experiencing health and safety problems. Community service methods were carried out through lectures, discussions, and mentoring. In the discussion, many were discussed about ergonomics, sitting position, use of bags, and the presence of gas cylinders in their homes. Furthermore, after this education, elementary students' understanding of K3 also increased.